2017
DOI: 10.1097/anc.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Collaborative Program for Neonatal Pain Management in Japan

Abstract: Background:Neonatal pain management guidelines have been released; however, there is insufficient systematic institutional support for the adoption of evidence-based pain management in Japan.Purpose:To evaluate the impact of a collaborative quality improvement program on the implementation of pain management improvements in Japanese neonatal intensive care units (NICUs).Methods:Seven Japanese level III NICUs participated in a neonatal pain management quality improvement program based on an Institute for Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Two multicentric trials applied QI principles to improve neonatal pain management in the involved sites [ 23 , 24 ]. In both the studies, local groups were created, better practices were identified and implemented, and improvement over time at different involved sites was assessed but did not discuss site-specific processes or obstacles faced to implement the practices, as the current study does.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two multicentric trials applied QI principles to improve neonatal pain management in the involved sites [ 23 , 24 ]. In both the studies, local groups were created, better practices were identified and implemented, and improvement over time at different involved sites was assessed but did not discuss site-specific processes or obstacles faced to implement the practices, as the current study does.…”
Section: Discussionmentioning
confidence: 99%
“…Quality improvement (QI) principles have improved neonatal pain management practices [ 23 , 24 ]. In addition, the World Health Organization's (WHO) 2007 Framework for Action for strengthening health systems in developing countries identified quality as one of the key drivers for improved health outcomes and greater efficiency in health service delivery [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“… 24 A collaboration of 7 NICUs in Japan improved neonatal pain management through staff education, the use of objective pain scales within the electronic health record, and the implementation of best practice prescribing guidance. 25 Clinicians need to assess analgesia use after practice changes as increased opioid prescribing has also been observed following the implementation of neonatal pain and sedation protocols. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This may give us some implications for our pain management practice. 49 Most of the time, clinical workers may neglect neonates' parents, who worry deeply about their babies especially when undergoing painful procedures and so one program in Canada named Baby-Friendly Initiative was implemented. They made a five-minute videotranslated in Chinese language-played on websites, in which it is shown that babies undergoing blood collections while they were on breastfeeding, held skinto-skin and feeding sucrose by mouth.…”
Section: The Practices Of Neonatal Analgesia In Different Countriesmentioning
confidence: 99%